Mobility determination and estimation based on smartphones-review of sensing and system - Aljeroudi, Yazan; Legowo, Ari; Sulaeman, Erwin (Asian Research Publishing Network (ARPN), 2015)
Smartphones devices, due to its complex sensory capability and comparable processing power, have proven their capability of handling mobility-related applications. This article aims at addressing the need for research on the development of mobility determination and estimation systems based on smartphones. Essentially, three main types of systems are addressed: human activity recognition (HAR), physical activity monitoring and evaluation, and indoor navigation. Some systems are developed as stand-alone smartphone application, while others are augmented with auxiliary sensors to improve functionality and performance. This article shows the main challenges that researchers aim at resolving in developing satisfactory smartphone based mobility determination and estimation systems.